Telemetry leads harbor nosocomial pathogens - Safdar, Nasia; Drayton, Jennifer; Dern, Jessica; Warrack, Simone; Duster, Megan; Schmitz, Michelle (International Journal of Infection Control, 2012)
The healthcare environment is recognized as an increasingly important source of healthcare-associated infection. We undertook a microbiologic survey of patient-ready, cleaned telemetry leads at our institution and recovered pathogenic multidrug resistant bacteria, such as methicillin-resistant Staphylococcus aureus and vancomycin-resistant enterococcus from the leads. Telemetry leads are difficult to clean and disposable leads are preferable.